Study of The Initiation of Green Banking Practices at State-owned Bank - Lilik Handajani; Ahmad Rifai; L. Hamdani Husnan (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2019)
AbstractThis study aims to describe the initiation of green banking practices at state-owned banks by identifying reporting issues and the level of green banking disclosure as well as formulating the reporting domain and indicators of its activities. Content analysis is carried out on information related to green banking activities report in the annual report of BUMN banks for the period 2015-2017. The research findings reveal that state-owned banks have initiated green banking practices. The practices come in various forms of activity due to the absence of reporting guidelines and the trend to report green banking activities that have been increasing over the past 3 years. Indicators of green banking activities in state-owned banks can be grouped into several reporting domains namely, green products, green operations, green customers and green policies. The implications of the study argue that the initiation of green banking practices in the practice of green banking at state-owned banks can be a role model for initiating environmentally friendly bank practices. Moreover, it is expected that environmentally friendly bank practices can minimize business risks by reducing environmental and social risks by harmonizing economic, environmental and social interests in towards achieving sustainable finance. Keywords: state-owned bank, green banking, sustainable finance Kajian Tentang Inisiasi Praktik Green Banking Pada Bank BUMNAbstractPenelitian ini bertujuan untuk mendeskripsikan inisiasi praktik green banking pada bank BUMN dengan mengidentifikasi isu-isu pelaporan dan tingkat pengungkapan green banking serta merumuskan domain pelaporan dan indikator kegiatannya. Analisis isi dilakukan terhadap informasi yang berkaitan dengan pelaporan aktivitas green banking pada laporan tahunan bank BUMN periode 2015-2017. Temuan penelitian mengungkapkan bank BUMN telah melakukan inisiasi praktik green banking dengan bentuk aktivitas yang beragam karena belum adanya pedoman pelaporannya dan terjadi kecenderungan pelaporan aktivitas green banking yang semakin meningkat dalam kurun waktu 3 tahun terakhir. Indikator kegiatan green banking pada bank BUMN dapat dikelompokkan dalam domain pelaporan yang meliputi green product, green operational, green customer, dan green policy. Implikasi dari penelitian mengargumentasikan bahwa inisiasi praktik green banking pada bank BUMN dapat menjadi role model inisiasi praktik bank ramah lingkungan untuk meminimalkan risiko bisnis dengan mengurangi risiko lingkungan dan sosial dengan menyelaraskan kepentingan ekonomi, lingkungan dan sosial dalam mewujudkan keuangan berkelanjutan. Kata kunci: bank BUMN, perbankan hijau, keuangan berkelanjutan